The Gaya Belajar Siswa Kelas III Sekolah Dasar Negeri 218/IX Talang Duku - Karina Karin; Magdad Hatim; Ida Suryani (Jurnal Tunas Pendidikan, 2024)
Research on Learning Styles of Grade Three Students Introduction This research aims to explore the learning styles of grade three students at Sekolah Dasar Negeri 218/IX Talang Duku. The focus of this research is to understand the visual, auditory and kinesthetic learning styles of the students, and the impact of monotonous learning methods on their engagement. Type of Research This research is a descriptive qualitative research, which aims to provide a detailed understanding of students' learning styles. Data Collection The results of this study were obtained through: Observation, Interview, In-depth questionnaire, these techniques are carried out directly in the field to collect data from informants. Findings This research focused on the learning styles of third grade students at SD Negeri 218/IX Talang Duku. The results showed that students have varied learning styles, including visual, auditory, and kinesthetic preferences. Conclusion Based on the research results, it can be concluded that third grade students of SD Negeri 218/IX Talang Duku have diverse learning styles, including: Learning by listening to the teacher's explanation/seeing, Memorising by repeating reading, solving problems through discussion or group work, Actively engaging with the teacher and classmates, Taking notes on important subject matter.